Toxicological and Pharmacological Assessment of Godanti Bhasma - Dubey, Nitin; Dubey, Nidhi; Mehta, R.S.; Sharma, Praveen; Ghule, Santosh; Bhowmick, Mithun (Asian Journal of Chemistry, 2012)
Godanti bhasma is an ayurvedic herbal mineral formulation used as antiulcer and antipyretic drug in Indian traditional systems of medicine. Godanti bhasma was evaluated for its toxicity, antiulcer and antipyretic activity in experimental animals. The experimental paradigms used for antiulcer activity were cold restraint stress induce ulcer model and diclofenac induced ulcer model in rat. Yeast induce pyrexia model in rat was used for antipyretic activity. Acute oral administration of Godanti bhasma showed no mortality in mice in the period of 14 days. The animals were found to be safe up to a maximum dose of 2000 μg/kg body weight in acute toxicity studies. Godanti bhasma demonstrated significant (p < 0.001) protection of 44.72 % in cold restraint stress induced gastric ulcer and 45.35 % protection in diclofenac induced ulcer (p < 0.001). TBARS of stomach in ulcer induced rat was also reduced (p < 0.001) by Godanti bhasma but serum calcium level was not altered. A significant (p < 0.001) reduction in hyperpyrexia in rat was also produced by the bhasma. The results suggest that this ayurvedic preparation possess significant gastro protective and antipyretic activity in lower doses of therapeutic range and the effect is not dose dependent (p > 0.05).